Role of Serum Total PSA (Prostate Specific Antigen) and Free to Total PSA Ratio in the Diagnosis of Carcinoma Prostate (Bangladesh Journal of Medical Biochemistry, 2013)
The objective of the study was to evaluate and compare the role of total and free/total ratio of serum prostate specific antigen level in diagnosing carcinoma prostate. A cross sectional study was conducted at the Department of Biochemistry, Dhaka Medical College (DMC) with collaboration of the Department of Urology, Dhaka Medical College Hospital (DMCH), Dhaka from July 2008 to June 2009. This study was carried out on 60 patients above 50 years of age who attended the Department of Urology, Dhaka Medical College Hospital, complaining of irritative or obstructive lower urinary tract symptoms (LUTS) suspected as clinically benign prostatic hyperplasia (BPH) or cancer prostate. It was aimed to assess the role of total and free/total ratio of serum PSA in diagnosis of BPH and carcinoma prostate with reference to histological diagnosis. All the cases were evaluated by history, physical examination including digital rectal examination, serum prostate specific antigen level, transabdominal/ trans-rectal ultra- sonogram. From all patients, blood sample were collected before digital rectal examination or any per urethral manipulation. Final diagnosis was obtained by histo-pathological examination, specimen being obtained by perrectal biopsy with biopsy-gun. Histopathological examination detected prostate cancer in 20 out of 60 patient and 17 of these Cap 20 have a total PSA ? 4 ng/ml and only 3 have total PSA ? 4 ng/ml. 18 of these 20 have free to total ratio ?0.16 and 02 have f/t ratio ?0.16. Among 60 patients, 40 patients were detected BPH on histopathological diagnosis. 20 of these BPH patient have tPSA ? 4 ng/ml and 20 of BPH have tPSA ? 4 ng/ml. 38 of 40 BPH patient have f/t ratio >0.16 and 2 of 40 patient are f/t ratio ?0.16. Receiver operating characteristic analysis indicated a threshold f/t ratio ? 0.16 was optimum discriminatory level. The sensitivity of total serum PSA (at cut off value of >4 ng/ml) in correctly differentiating prostatic carcinoma of those who have the condition is 85%, while the specificity of the test in correctly detecting those who do not have the disease is 50%. The PPV is 45.9%, NPV is 87% and accuracy is 61.7%. The sensitivity of free/total serum PSA (at cut off value of 0.16 ng/ml) in correctly differentiating prostatic carcinoma from BPH is 90%, while the specificity of the test in correctly detecting those who do not have prostatic carcinoma is 95%. The PPV of the test is 90% and the NPV of the test is 95%. The overall accuracy of the test is 93.3%. This study showed significant difference of total and free/total ratio of serum prostate specific antigen (PSA) in differentiating benign prostatic hyperplasia (BPH) from carcinoma prostate. Receiver operating characteristic curves showed advantage for the f/t PSA ratio when compared with total PSA in detecting prostate cancer. From the study it may be concluded that total and f/t ratio of prostate specific antigen (PSA) is a useful marker in diagnosis of carcinoma prostate. Free/total ratio is more accurate than total PSA. DOI: http://dx.doi.org/10.3329/bjmb.v4i1.13778 Bangladesh J Med Biochem 2011; 4(1): 21-26